The land of stories : beyond the kingdoms / 4. - Colfer, Chris, 1990- (Land of stories, 2015)
"The Masked Man possesses a powerful magic potion that turns every book it touches into a portal, and he is recruiting an army of literature's greatest villains! So begins a race through the magical Land of Oz, the fantastical world of Neverland, the madness of Wonderland, and beyond. Can twins Alex and Conner catch up to the Masked Man?"--Provided by publisher.